Differential composition of lymphocyte subpopulations and activation between the hypertensive Bph/2 and normotensive Bpn/3 mouse strains - Dattmore, Devon; McDonald, Paiton O.; Chowdhury, Afrin; Awali, Saamera; Boss, Allison P.; Jin, Yining; Sather, Lisa; Lauver, D. Adam; Rockwell, Cheryl E. (Frontiers in Immunology, 2026)
IntroductionNumerous studies point to a role for the immune system in various animal models of hypertension. However, little is known about the immune system of Bph/2 mice, a spontaneously hypertensive strain.MethodTo address this, we conducted a comprehensive comparison of immune cell composition and response to polyclonal T cell activation in hypertensive Bph/2 mice and normotensive Bpn/3 control mice. We quantified immune cell populations by flow cytometry from spleen and inguinal, brachial and mesenteric lymph nodes.ResultsWhile composition of myeloid immune cell types was largely comparable between strains, we observed differences in B and T cell subpopulations. Specifically, we found an increased percentage of IgM+ IgDLo and IgM+ IgD- B cells in Bph/2 mice, suggesting greater baseline B cell activation or differences in B cell lineage. In addition, we observed a decreased percentage of CD4 effector memory T cells and CD8 central memory T cells. The diminished proportion of memory T cells in Bph/2 mice correlated with decreased proliferation and cytokine response of splenic T cells to polyclonal T cell activation. In splenic T cells from Bph/2 mice 24 h after activation, we observed a pronounced decrease in the majority of T cell cytokines. At 120 h after activation, the Th1 and Th17 cytokine responses of splenic T cells from Bph/2 mice were decreased, but other T cell cytokines were largely comparable between genotypes.Conclusion/DiscussionOverall, the data suggest a decreased percentage of memory T cells in Bph/2 mice that correlates with markedly diminished proliferation and cytokine response to polyclonal activation.